الغضب لدى المعاقين سمعيا تبعا لمتغيري الجنس والمستوى التعليمي "دراسة ميدانية في محافظة اللاذقية" - سليمون ريم; صبيرة فؤاد; حلوم نسرين (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The research aims to understand anger among the hearing-impaired according to the variable of sex and education level. The research problem is summarized in the following question: Does the degree of anger vary with the hearing-impaired in the city of Lattakiadepending on the variables of the study? The total sample consisted of 50 hearing-impaired kids.They wereselected randomly from the Institute of Special Education for the acoustically disabled and from some private centers. The anger scale (prepared by the researcher) was applied to get the data of the sample according to a set of statistical methods (Alpha Krumbach coefficient and retail midtermand test the significance Stodnt t-test).The research reached the following results: 1.There were no statistically significant differences between the mean scores of the hearing- impaired anger scale depending on the variable of sex. 2.There were some significant differences between the mean scores of the hearing-impaired on the anger scale variable depending on the level of education. يحاول هذا البحث التعرف على الغضب لدى المعاقين سمعيا تبعا لمتغيري الجنس و المستوى التعليمي , وتتلخص مشكلة البحث بالسؤال التالي: هل تختلف درجة الغضب لدى المعاقين سمعياً في مدينة اللاذقية باختلاف متغيرات الدراسة ؟ لتحقيق أهداف هذا البحث تم استخدام المنهج الوصفي على عينة قوامها 50 طفل وطفلة من المعاقين سمعياً، وتم سحب العينة بالطريقة العشوائية من معهد التربية الخاصة للمعوقين سمعياً و من المراكز الخاصة، و استخدم مقياس الغضب (إعداد الباحثة) للحصول علــــــى البيانات مـــــــن أفراد العينــــــة كما تــــم استخدام مجموعــــــة مـــــــن الأساليب الإحصائيـــــة (, معامــــل ألفا كرومباخ, والتجزئة النصفية، واختبار الدلالــــــــة t-test ستودنت ) وتوصل البحث للنتائج التاليــــة: 1- لا توجد فروق ذات دلالة إحصائية بين متوسطات درجات المعاقين سمعياً على مقياس الغضب تبعاً لمتغير الجنس. 2- توجد فروق ذات دلالة إحصائية بين متوسطات درجات المعاقين سمعياً على مقياس الغضب تبعاً لمتغير المستوى التعليمي.